A human pathogenic hantavirus circulates and is shed in taxonomically diverse rodent reservoirs. - Samuel M Goodfellow; Robert A Nofchissey; Chunyan Ye; Jaecy K Banther-McConnell; Thanchira Suriyamongkol; Joseph A Cook; Jonathan L Dunnum; Ivana Mali; Steven B Bradfute (PLoS Pathogens)
Background Orthohantaviruses are negative-sense RNA viruses that can cause hantavirus cardiopulmonary syndrome (HCPS) in humans. In the United States, Sin Nombre orthohantavirus (SNV) is the primary cause of HCPS, with a fatality rate of 36% and most cases occuring in the southwestern states. The western deer mouse, Peromyscus sonoriensis, is the primary reservoir for SNV; however, it remains unclear if alternative reservoirs exist. Results We conducted an extensive survey of SNV genetic prevalence in wild-caught small mammal communities throughout New Mexico and observed that 27% of all animals were positive for SNV. Through longitudinal trapping at a site of patient exposure, we found that SNV circulates at a high rate in multiple species over time. Furthermore, we isolated live SNV from tissues and feces from multiple small mammal species, demonstrating infectious virus in alternative and novel reservoirs. Significance Altogether, this work shows that SNV is widely prevalent and persistent throughout New Mexico in multiple small mammal reservoirs that can harbor and shed infectious virus. This encourages future work for additional surviellance efforts and revaluates host-species dynamics for New World hantaviruses.